2006
DOI: 10.1300/j484v12n01_02
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Fruit Yield and Quality ofTrichosanthes cucumerinaLandraces to Phosphorus Rate

Abstract: Snake Gourd (Trichosanthes cucumerina L.), a member of the Cucurbitaceae, also locally known as Snake Tomato, has qualities that could make it a potential substitute for the solanaceous tomato [Lycopersicon esculentum (L.) Mill.], especially when the latter is not available during the year. However, there is little known about the mineral nutrition requirements of Snake Gourd, and how nutrition affects fruit yield and quality. Studies were conducted from University, Ile-Ife, Nigeria to evaluate the effect of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The dry matter contents of the pulp of Morphotype I (V1) and Morphotype II (V2) were 10.9 and 9.6 g/100g FW, while the ascorbic acid contents were 25.7 and 24.8 mg/100 g FW, respectively (Table 1). These values are consistent with those reported by Adebooye et al (2005) and Adebooye and Oloyede (2006) for the same morphotypes of T. cucumerina. The dry matter values are higher when compared with the dry matter contents of 8.3 g/100 g FW and 5.3 g/100 g FW reported for Aranca tomatoes and Excell tomatoes, respectively by Sahlin et al (2004).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The dry matter contents of the pulp of Morphotype I (V1) and Morphotype II (V2) were 10.9 and 9.6 g/100g FW, while the ascorbic acid contents were 25.7 and 24.8 mg/100 g FW, respectively (Table 1). These values are consistent with those reported by Adebooye et al (2005) and Adebooye and Oloyede (2006) for the same morphotypes of T. cucumerina. The dry matter values are higher when compared with the dry matter contents of 8.3 g/100 g FW and 5.3 g/100 g FW reported for Aranca tomatoes and Excell tomatoes, respectively by Sahlin et al (2004).…”
Section: Resultssupporting
confidence: 92%
“…These differences could be attributed to genotype. Previous studies by Adebooye et al (2005), Adebooye and Oloyede (2005) and Oloyede and Adebooye (2006) have shown clear genotypic differences between the two morphotypes of T. cucumerina. The higher FRAP obtained for V2 in this study could be attributed to its higher contents of phenolics and flavonoids compared to V1.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…It is commonly called snake gourd, viper gourd, snake tomato or long tomato [2]. The endocarp pulp when fully mature is sweet tasting, aromatic and deep red which does not go sour as quickly as the paste of S. lycopersicum, this account for the reason why it is employed as an alternative to the Solanaceous tomato [3].…”
Section: Introductionmentioning
confidence: 99%